COVID-19 Vaccine Acceptance and Its Determinants among Medical Students at the Universiti Malaysia Sabah: A Cross-Sectional Study - Abdul Rahman Ramdzan; Mohd Rushadi Mohd Shahrin; Er Huey Cheen; Manween Kaur Bakhs’hiss’h Singh; Erni Ariffarhani Selamat; Effie Carmella Norbertus; Aathinii Mathialagan; Muhammad Yaqiz Yaacob; Zulkhairul Naim Ahmad Sidek; Nuurain Amirah Mohd Razi (Universiti Putera Malaysia, 2023)
Malaysia has announced the COVID-19 National Immunization Programme (NIP) involving three phases beginning in March 2021, with the target of vaccinating 80 percent of the population. The purpose of this study was to determine whether medical students at the Faculty of Medicine and Health Sciences (FMHS), Universiti Malaysia Sabah (UMS), were accepting of the COVID-19 immunization and the factors that may have contributed to that acceptance. Methods: A cross-sectional online study involving 244 medical students from FMHS, UMS, was carried out utilizing a validated electronic questionnaire. The questionnaire was divided into three sections: variables influencing COVID-19 vaccine acceptability, sociodemographic characteristics of the students, and their acceptance of the vaccine. The IBM Statistical Package for Social Sciences (SPSS) was used to statistically analyze the data. Results: 91.4% of people accepted the COVID-19 vaccine, which is among the highest rates among studies done in academic settings. Vaccine information from health agencies was found to be significantly associated with the acceptability of the COVID-19 vaccination (p=0.02) and confirmed by multivariable analysis as its determinant (prevalence odds ratio 9.535, 95% confidence interval 3.931-15.138, p-value: 0.004). Conclusion: This study merits the attention of the public health department of FMHS, UMS to plan cooperative synergy with regional health organizations like the Malaysian Health Coalition (MHC) to improve knowledge and raise awareness about the COVID-19 vaccination while also giving medical students evidence-based information.